Carbon nanotubes integrated into polyamide membranes by support pre-infiltration improve the desalination performance - Guvensoy-Morkoyun, Aysa; Kurklu-Kocaoglu, Suer; Yildirim, Cansu; Velioglu, Sadiye; Karahan, H. Enis; Bae, Tae-Hyun; Tantekin-Ersolmaz, S. Birgul (Pergamon-Elsevier Science Ltd, 2021)
Carbon nanotubes (CNTs) are promising for realizing ultrafast membranes with implications to molecular separations and beyond. However, it is a big challenge to harness the potential of CNTs for designing scalable yet high-performance membranes. Here we systematically explore the role of loading and vacuum-assisted alignment of CNTs for improving the desalination performance of polyamide (PA) based thin-film composites. To rule out the dispersion instability issues, we focused on carboxylated single-walled CNTs (SWCNTs) commercially available in the market. After applying a pre-treatment for clean-ing, we deposited SWCNTs on porous polysulfone supports by vacuum filtration and coated a PA layer on top via interfacial polymerization. Morphological assessments supported by polarized Raman micro-spectroscopy allowed the quantification of SWCNT alignment. At an optimum SWCNT loading, which we found critical for alignment, the water permeability of resulting membranes significantly improved without compromising NaCl selectivity. Also, we achieved an improved boric acid selectivity, arguably owing to the hydrophobic nature of nanotube channels. Moreover, nanotubes promoted resistance against chlorine degradation and improved mechanical strength. Vacuum deposition is instrumental for infiltrating SWCNTs into the support layer, but a mat layer forms between the support and PA layers when SWCNT loading exceeds the limit that the support pores can accommodate. Given that we use ordinary SWCNTs and a scalable methodology (vacuum-assisted infiltration), the developed membranes are promising for practical applications. (c) 2021 Elsevier Ltd. All rights reserved.
Keywords: Single-walled carbon nanotubes; Interfacial polymerization; Thin film nanocomposite; Reverse osmosis; Desalination; Boron removal